Spontaneous Pneumothorax Associated with Covid-19 Infection: A Case Series - Kandel, Sanjog; Karki, Manoj; Rayamajhi, Bidhata; Chaudhary, Shatdal; Jaiswal, Niraj Kumar; Gautam, Narayan (Journal of Universal College of Medical Sciences, 2022)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) virus, which mostly affects the respiratory system. As a result of the inﬂammatory response, mortality and morbidity are linked to fast clinical deterioration. Pneumothorax is a rare complication in COVID-19 patients that might exacer- bate the patient's hypoxia and necessitate rapid treatment. It is critical to evaluate alternate diagnosis and repeat imaging in individuals with SARS-CoV-2 who have seen an abrupt worsening. We present a case series of four individuals who had spontaneous pneumothorax despite having no other risk factors for pneumothorax other than recent COVID-19 infection.